Distribution and demography of Antarctic krill and salps in the Atlantic sector of the Southern Ocean during austral summer 2021-2022 - Bitiutskii, Dmitrii G.; Samyshev, Ernest Z.; Minkina, Natalia I.; Melnikov, Victor V.; Chudinovskih, Elena S.; Usachev, Sergei I.; Salyuk, Pavel A.; Serebrennikov, Alexander N.; Zuev, Oleg A.; Orlov, Alexei M. 1960- (Water)
The study aimed to investigate krill (Euphausia superba) and salp (Salpa thompsoni) populations in the Atlantic sector of the Southern Ocean in January and February 2022. Samples were obtained to measure the abundance, biomass and distribution patterns of krill and salp. Sex differences and feeding habits of the Antarctic krill were determined. The dependence of the physiological state of the studied aquatic organisms on changes in environmental parameters was analyzed. Current data on the association of the dynamics of hydrometeorological parameters and processes with the distribution of chlorophyll a, krill, and salp were obtained. It was established that, at numerous stations, the biomass of salps prevailed over krill. The result indicates the replacement of the Antarctic krill populations by gelatinous zooplankton. The obtained results allow assessment of the biological resource potential in the studied region based on the analysis of the samples collected.